The mechanical behavior of salt : understanding the THMC processes in salt : proceedings of the 6th Conference on the Mechanical Behavior of Salt 'Saltmech6', Hannover, Germany, 22-25 May 2007 /: understanding the THMC processes in salt : proceedings of the 6th Conference on the Mechanical Behavior of Salt 'Saltmech6', Hannover, Germany, 22-25 May 2007. (2017) - Unknown
No abstract available